What is new in anaphylaxis? - Martelli, Alberto; Ippolito, Rosario; Votto, Martina; De Filippo, Maria; Brambilla, Ilaria; Calvani, Mauro; Cardinale, Fabio; Chiappini, Elena; Duse, Marzia; Manti, Sara; Marseglia, Gian Luigi; Caffarelli, Carlo; et al. (Acta Biomedica Atenei Parmensis, 2020)
Available information suggests that anaphylaxis must be promptly recognized keeping in mind the airway patency, breathing (ventilation and respiration), circulation and mental status and treated. The first treatment is adrenaline. After successful treatment of an anaphylactic episode, attention must be paid to the prevention of early recurrences (biphasic anaphylaxis) and assessment of causes. Children should not be discharged before prescribing self-injectable adrenaline and explain how and under what circumstances it must be injected, An action plan must be communicated to their communities. Inform the school about potential reactions, how to prevent them and avoidance measures.